(3HgLI GdfGXQjf Edi JQGLe GdeJCNQjf ef GdTGaYjI GdHGQYjfs - (3eMeO Hf CMeO Hf YHO Gddg Hf HOQ, CHh GdHQcGJ, QVj GdOjf GHf TgGH GdOjf GdYGeQj GdZRj,J (B864 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eOHQ GdCehQ , eejJ GdCMjGA , hHGYK ef ai GdbHhQ (B,(3GdN s
(3BNQgG (B:s
(3aeG cGf ef UhGH aef Gddg , heG cGf ef NWC hRdI aefi hef GdTjWGf YUefG Gddg JYGdi efg hef SGFQ GdCYOGA Bejf s
(3fSNI KGfjIs
(3fSNI efbhdI ef NW GdeDda HETGQI hdOg GdbGVi TgGH GdOjfs
(3hbO JQc ai HYV GdCeGcf aQGZ dedFg ajeG HYO ceG TWH Ydi HYV GdYHGQGJs
(3hGdejcQhajde Hg Jda HSjWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B333 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B279s
Keywords: (3GdJGQjNs